A practical approach to the investigation of the hyperprolactinaemic patient. Issue 670 (August 1981) - Shalet, S. M.; Chapman, A. J.; Whitehead, E.; Beardwell, C. G.
Abstract : Pituitary function was assessed in 39 patients with previously untreated hyperprolactinaemia. Primary hypothyroidism, drug-induced hyperprolactinaemia and chronic renal failure were excluded in all patients. All of the 22 patients (group 1), who had either a normal pituitary fossa or a minor radiological change on lateral skull X-ray, had completely normal pituitary function with the exception of 2 who were partially growth hormone-deficient. However, 9 of the 17 patients with macroadenomas (group 2) had a deficit of one or more anterior pituitary hormones. After the lateral skull X-ray 13 patients in group 1 had further neuroradiological investigations. In only one was a minor abnormality noted which had not been observed on the plain film and this was not of practical significance. In centres where hyperprolactinaemic patients with a normal pituitary fossa or a minor radiological change on lateral skull X-ray are treated with bromocriptine, further neuroradiological investigations and dynamic tests of pituitary function are not required.